Catalyzing purposeful transformation: The emergence of transformation catalysts. (28th February 2022) - Waddock, Sandra
Abstract: This op ed argues that the pandemic has highlighted the emergence of a new type of entity called a transformation catalyst (TC). TCs help collections of initiatives with similar agendas see and understand their system, connect to like‐minded others to develop coherence for their efforts, and thereby amplify their impact by working in coherence and sometimes coordinated—yet independent—ways. Such efforts around issues like reframing the purpose of business or efforts to transform business sectors are enhanced and their effectiveness catalyzed by TCs. TCs work by helping initiatives see and understand their system, connect with like‐minded others, and cohere their efforts. These activities can amplify the impacts of initiatives to bring needed system transformation into being.